Effect of alkali concentration on functionality, lysinoalanine formation, and structural characteristics of tea residue proteins. (15th October 2018) - Ayim, Ishmael; Ma, Haile; Alenyorege, Evans Adingba; Ali, Zeshan; Zhou, Cunshan; Donkor, Prince Ofori
Abstract: The effect of varying sodium hydroxide concentration on functionality, structural characteristics, and the generation of lysinoalanine from tea protein extraction was explored. The results indicated that increasing alkali molarity from 0.0125 to 0.150 M resulted in an increase in protein yield, solubility, foam capacity, and stability up to 0.1 M, which declined further with an increase in the alkali concentration. Surface hydrophobicity, thiol, and disulfide contents reached a maximum at 0.075 M and continued to decline afterward. The effect of alkaline concentration on lysinoalanine (LAL) formation showed an increase from 6.00 ± 0.32 g/kg at 0.1 M to 29.43 ± 1.10 g/kg at 0.125 M followed by a decline to 7.37 ± 0.01 g/kg at 0.15 M. There was a significant ( p < .05) reduction in Cys and Lys contents as alkali concentration increased. The use of alkali in extracting protein from tea and other plant sources should be monitored as higher alkali concentration may pose a nutritional concern. Practical applications: Extraction of protein from plant sources is most often facilitated by use of alkali. However, the adverse effect of use of alkali is not considered in most cases. The use of sonication, ethanol, and Viscozyme pretreatments coupled with varying alkali concentration was adopted to extract proteins from tea residue and the generation of lysinoalanine, a toxic substance was quantified. The use of alkali at higher concentrations could pose a nutritional concern as it caused an increase in lysinoalanine content. Improved protein yield and purity can be achieved at moderately lower alkali concentrations.